Differential Diagnosis of ICD-11 Personality Disorder and Autism Spectrum Disorder in Adolescents - Bo Bach; Martin Vestergaard (MDPI AG, 2023)
The International Classification of Diseases 11th Revision (ICD-11) introduces fundamentally new diagnostic descriptions for personality disorder and autism spectrum disorder. Instead of the traditional categorical taxonomies, both personality disorder and autism spectrum disorder are described as being on a continuum. Accumulating research has pointed out that, in some cases, adolescents with autism spectrum disorder are at risk of being confused with having a personality disorder, which particularly applies to female adolescents. Case reports describe how adult autistic women struggled with social and identity roles as children and adolescents, using compensatory strategies such as social imitation and other types of camouflaging. Furthermore, some adolescents with autism display emotion dysregulation and self-injury. The ICD-11 recognizes that features of autism spectrum disorder may resemble features of personality disorder, but the two diagnoses have not yet been formally compared to one another. The present article therefore sought to outline and discuss the overlap and boundaries between the ICD-11 definitions of personality disorder and autism spectrum disorder and propose guiding principles that may assist practitioners in differential diagnosis with female adolescents. We specifically highlight how aspects of the self and interpersonal functioning along with emotional, cognitive, and behavioral manifestations may overlap across the two diagnoses. Restricted, repetitive, and inflexible patterns of behavior, interests, and activities are core features of autism spectrum disorder, which may be masked or less pronounced in female adolescents. Collecting a developmental history of the early presence or absence of autistic features is vital for a conclusive diagnosis, including features that are typically camouflaged in females. A number of future directions for research and clinical practice are proposed.